Insights into silicon cycling from ice sheet to coastal ocean from isotope geochemistry - Katharine R. Hendry; Felipe Sales de Freitas; Sandra Arndt; Alexander Beaton; Lisa Friberg; Jade E. Hatton; Jonathan R. Hawkings; Rhiannon L. Jones; Jeffrey W. Krause; Lorenz Meire; Hong Chin Ng; Helena Pryer; et al. (Communications Earth & Environment)
Abstract The polar regions are biologically productive and play a critical role in regional and global biogeochemical cycling. A key nutrient is dissolved silicon, required for the growth of siliceous phytoplankton, diatoms, which form an important component of polar ecosystems. Glacial weathering is thought to be an important dissolved silicon source to coastal waters, especially critical in regions experiencing seasonal silicon limitation of diatom growth. However, complex physical and biogeochemical interactions in fjords and coastal regions modulate the downstream supply of dissolved and particulate nutrients, including silicon. Here, we review the biogeochemical complexities of glaciated margins and the insights into this system that silicon isotope geochemistry offer. We show that stable and radioisotopic measurements and biogeochemical numerical modelling provide a quantitative mechanistic understanding of subglacial silica mobilisation and its cycling across the land-ocean continuum. Subglacial weathering produces isotopically light amorphous silica, which dissolves in seawater to release dissolved silicon. Our findings show that isotopically light, detrital silica, likely containing glacial material, reaches the ocean and there could support a substantial proportion of diatom productivity, especially in the Arctic. Outstanding questions about silicon cycling in these crucial environments will be addressed through novel and cross-discipline approaches that overcome traditionally viewed ecosystem boundaries.